PENGARUH TEKNIK BRAINSTORMING MENGGUNAKAN LKPD TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KOMUNIKASI MATEMATIS DENGAN MEMPERHATIKAN GAYA BELAJAR SISWA KELAS XI MIA SMAN 1 LUBUK BASUNG - Utami, Khurnia Budi (journal of RESIDU, 2018)
The specific target to be achieved in this study is that it can describe the mathematical abilities of high school students of class XI MIA based on the learning styles they have through learning with brainstorming techniques, produce LKPD and RPP in accordance with learning with brainstorming techniques, published in unaccredited national journals, attend seminars national and produce national seminarproceedings l. The research is a quasi experimental research (quasy-experiment), quasy experiment for the selected sample group is already in the form of groups and researchers may not form a group again. In this study used two groups that became the sample, the experimental group that will get treatment with brainstorming techniques and the control group that gets conventional learning. Based on the results of the study, several conclusions were obtained. First, students' problem solving and mathematical communication skills taught by brainstorming techniques are better than students taught with conventional learning. Second, students' problem solving abilities in visual and kinesthetic learning styles taught by brainstorming techniques are better than students taught with conventional learning, but there is no difference in problem solving abilities of auditory learning students taught by brainstorming techniques and those taught with conventional learning. Third, students' mathematical learning skills in visual and kinesthetic learning styles are taught by brainstorming techniques better than students taught with conventional learning, but there is no difference in mathematical communication skills of auditory learning style students taught bybrainstorming techniques and those taught with conventional learning. Keyword: Brainstorming technique, learning style, mathematical ability